The Urgency of Mimetic Studies: From Imitation to (New) Fascism. Girard Lecture - Lawtoo, Nidesh (HOM Videos ERC Project Homo Mimeticus, 2024)
In this 5th biannual Girard lecture, organized by the Dutch Girard Society, Nidesh Lawtoo steps back to the insights that, as of 2016, lead him to use the term “(new) fascism” as a warning against Donald Trump’s anti-democratic tendencies, which culminated in an insurrection on January 6. Despite many critical warnings and fascist actions, the efficacy of the affective and infective powers of mimesis never ceases to surprise. Hence, the urgency of new mimetic studies to reflect on the role imitative phenomena left in the shadow by Girard -from crowd behavior to hypermimetic media to the patho(-)logies of mimetic theory itself generated by figures like J. D. Vance - play in the contemporary re-turn of (new) fascist leaders in the US, Europe and beyond.